Carotid Plaque Rupture Is Accompanied by an Increase in the Ratio of Serum circR-284 to miR-221 Levels - Bazan, Hernan A.; Hatfield, Samuel A.; Brug, Aaron; Brooks, Ashton J.; Lightell, Daniel J.; Woods, T. Cooper (Circulation. Cardiovascular genetics, 2017)
BACKGROUND—Atherosclerotic plaque rupture is accompanied by an acute decrease in the carotid plaque expression of micro-RNAs (miRs)-221 and miR-222. Circular RNA (circR)-284 is a potential inhibitor of miR-221/miR-222 activity. We aimed to determine whether changes in the serum levels of these noncoding RNAs are observed in patients with asymptomatic high-grade carotid disease versus patients with acutely symptomatic carotid disease and recent ischemic stroke. Additionally, we tested the use of functionally related noncoding RNA pairs to enhance the discriminatory power of noncoding RNAs as circulating biomarkers. METHODS AND RESULTS—Serum levels of miR-221, miR-222, miR-145, and circR-284 were measured in 24 asymptomatic (asymptomatic) and 17 acutely symptomatic patients ([urgent] ischemic cerebrovascular event within the previous 5 days) undergoing carotid endarterectomy. miR-221 was significantly lower, whereas circR-284 was elevated in the serum of the urgent compared with the asymptomatic group. The ratio of serum circR-284:miR-221 was significantly elevated in the urgent group (P=0.0002) and exhibited favorable characteristics as a biomarker indicative of carotid plaque rupture and stroke. A validation study in 112 patients (47 asymptomatic, 41 urgent, and 24 patients with a cerebrovascular event between 5 and 180 days of the carotid endarterectomy [symptomatic]) confirmed elevation of serum circR-284:miR-221 uniquely in the urgent group (P<0.001) and favorable sensitivity and specificity for detecting plaque rupture and stroke. CONCLUSIONS—Serum circR-284:miR-221 has potential as a diagnostic biomarker of carotid plaque rupture and stroke. Moreover, we demonstrate the use of functionally related pairs of circulating noncoding RNAs as biomarkers in cardiovascular disease.